LEGAL PROTECTION IN INDONESIA OF ONLINE RIDE-HAILING DRIVERS AND DIGITAL FREELANCERS IN THE GIG ECONOMY ERA - Indra Wijaya; Thi Kim Nguyen (SYNTIFIC, 2026)
Background. Digital economy has fundamentally transformed labor relations worldwide. In Indonesia, digital platform-based work has become an increasingly important source of employment, particularly for online ride-hailing drivers, delivery couriers, and freelance digital workers. While digital platforms offer flexibility, they also generate significant legal challenges concerning employment status, social protection, occupational safety, income security, and collective labor rights. Most platform companies classify workers as independent partners rather than employees, thereby excluding them from labor protections traditionally afforded under employment law. This study examines the adequacy of Indonesia's legal framework in protecting digital platform workers and identifies regulatory gaps affecting labor rights in the gig economy. Research Methods. The statutory approach examines relevant Indonesian legal instruments, including Law No. 13 of 2003 concerning Manpower, Law No. 6 of 2023 concerning Job Creation, Law No. 24 of 2011 concerning Social Security Administration, and relevant regulations governing transportation and digital platforms. The conceptual approach explores theories of labor protection, employment relationships, economic dependency, social justice, and algorithmic management. The comparative approach examines regulatory developments in jurisdictions that have introduced specific protections for platform workers. Findings. Indonesia's existing labor law framework does not adequately accommodate platform-mediated work relationships characterized by algorithmic management and economic dependency. Consequently, many digital platform workers remain excluded from minimum wage protection, social security benefits, occupational safety guarantees, and collective bargaining mechanisms. Conclusion. The establishment of a dedicated regulatory framework recognizing platform work as a distinct labor category while ensuring fundamental labor rights and social protection standards.